Psychological diversity of young judo adepts on the example of girls and boys - Patrycja Janowska; Marta Wojdat; Emilia Bugajska; Magdalena Paradowska; Robert Stępniak (Kazimierz Wielki University, 2018)
Aim: To verify if young judo adepts show any signs of psychological diversity in case of sex, as any possible differences can be a valuable material for coaches who work with young boys and girls who start their career in sport. Material and methods: The group of 30 young boys who practice judo in Bydgoszcz and in smaller towns around and the group of 26 young girls who also practice judo in Bydgoszcz and in smaller towns around were tested. The, so called, 'Brown Test' by prof. W. Starosta of The Sport Way Academy was used. Results: There were important differences observed among two measured variables. Conclusion: The Brown Psychological Test differs in some cases researched persons because of sex and shows some psychological reserve area.